A proposed expansion of the Library of Congress schedule DS 651 to DS 689 for Philippine history - Lee, Verna C.; Faderon, Rosalie B.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1988)
The Library of Congress Classification scheme was developed basically for the needs of the users and staff of the Library of Congress. Hence, the applicability of the system to other library situations is limited and inadequate. For Philippine libraries in particular, the LCC division DS651-689 for Philippine history and description fails to meet the current classification needs of Philippine history materials.
The study aims to provide an expanded version of the LCC DS651-689 schedule. It specifically: a) provides classification numbers for subjects which are not reflected in the DS schedule; b) expands the historical periods and events which were insufficiently constructed to correspond to past as well as to present-day situations; c) develops the auxiliary tables for individual biography, regions, provinces, cities, municipalities and elements in the population (ethno-linguistic and minority groups); d) provides sufficient explanatory and scope notes to classification numbers to eliminate ambiguities and confusion; and e) provides an index to the schedule for quick and easy use.
Three methods of expanding the schedule were adapted. These are: 1) the expansion of the existing class numbers decimally in the present schedule, 2) the adaption of new class numbers or subjects not presented in the schedule, and 3) further use of Cutter numbers.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Classification -- Books -- Philippines -- History; Classification, Library of Congress